Teaching Factory Based on Scientific Creativity to Enhance Students' Soft Skills and Sustainable Entrepreneurship - Samsuri, Taufik; Habibi, Habibi; Ikhsan, Muhamad (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This study aimed to assess the validity and effectiveness of a Teaching Factory (TEFA) model based on scientific creativity in enhancing students’ soft skills and fostering sustainable entrepreneurship. The TEFA approach was validated through expert evaluations and tested through two production processes involving 15 university students. The research focused on improving soft skills such as communication, teamwork, creativity, leadership, and time management, alongside sustainable entrepreneurship skills like opportunity identification, resource utilization, and entrepreneurial action. Data were collected using observation sheets and analyzed through descriptive statistics and ANOVA to compare students' performance across the two production processes. The results showed significant improvements in students' soft skills and sustainable entrepreneurship, with the TEFA approach based on scientific creativity proving highly effective. Average soft skill scores increased from